Assistance in Processing Polyethylene Terephthalate (PET) Strapping Waste into Economically Valuable Handicrafts for The Community of Dayu Village, Gondangrejo Subdistrict, Karanganyar Regency - Hadibasyir, Hamim Zaky; Priyono, Kuswaji Dwi; Kiat, Umar El Izzudin; Sari, Dewi Novita; Wibowo, Afif Ari; Anggani, Nirma Lila (Universitas Muhammadiyah Surakarta, 2025)
Dayu Village, located in Gondangrejo Subdistrict, Karanganyar Regency, faces challenges in infrastructure development and area management, alongside high unemployment rates and low community skills. To address these issues, a community service activity was conducted with the aim of providing assistance in processing polyethylene terephthalate (PET) strapping waste into economically valuable handicrafts to enhance residents' skills and income. The implementation method included pre-activity coordination with village government and community members, direct training in crafting products from PET waste, and evaluation and follow-up through discussions and aspiration gathering. The activity was attended by 19 participants who successfully produced marketable waste basket crafts. This initiative opened opportunities for Dayu Village residents to earn additional income through PET strapping waste processing. The high enthusiasm and hope expressed by participants indicate a desire for the activity to continue as a sustainable economic empowerment program in Dayu Village.